General practitioner’s (GP) home management guidelines for COVID-19 patients: Guidelines - Aisha Ambreen; Tabinda Ashfaq; Marie Andrades; Fauzia Akhtar; Sadaf Badiuzzaman; Lubna Baig (Journal of the Pakistan Medical Association, 2021)
Carefully developed guidelines for clinical practice serve as an important tool for desirable changes in health care of a country. They act as an important source of information for physicians as well as policy makers and educational institutions thereby improving quality of care of patients. The outbreak of Novel Coronavirus Disease (COVID-19) in 2019 has placed huge burden on health care system globally. The first line health care provider bears the brunt of this disease with limited and varying sources of information as most of the patients present to them. Varied presentation of disease along with limited hospital facilities for admission is a huge challenge for appropriate management and referral of these patients. These guidelines, prepared after reviewing the interim guidelines in literature, will serve as a source of guidance for GPs to manage mild cases at home and refer those with moderate and severe disease to tertiary... Continuous...